Women in View West Law and Islamic Law - Arifin, Zarul (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2021)
Studies on women from time to time continue to emerge. Recently, with the proliferation of discourses on feminism in various parts of the world, women and their existence have returned to the lips of our society. Feminism with its idea of equality, in theory and practice, is not uniform. Even though the word equality is often discussed and studied in depth, there has been no satisfactory media formula, which is generally agreed upon. West and Islam, for example, have their own formulations and interpretations regarding women's equality. More cautious and far-sighted striving for women's equality on the one hand without eliminating that womanly nature, on the other hand, in contrast to the west, equality is interpreted as broadly as possible so that women who initially feel happy with the freedom offered, in turn, are trapped in the form of equality This journal that exploits and eliminates its female nature is one of the moral messages of this journal that in responding to an offer of freedom we should consider and examine more deeply. It is certain that Muslims themselves in carrying out these considerations must be based on the rules and laws of Allah stated in the Al Quran. and Sunnah. Some of the things discussed in this journal are: Legal sources of women's rights and obligations in Islamic law and European society, the position of women in Islam, the discourse of difference and equality.Keywords. Women, West, Â law, Islamic, Â Law.